Effects of l-arginine supplementation with high-intensity training on muscle damage and fatigue index and athletic performance in Canoe Athletes - Jung, J.-H.; Kang, E.-B.; Kim, C.-H. (Journal of the Korean Applied Science and Technology, 2019)
The objective of this study was to evaluate the effects of L-arginine supplementation on muscle damage and fatigue indices and athletic performance improvement of canoe athletes after conducting a high-intensity training program. To achieve the objective, this study applied a high-intensity training program to seven high school canoe athletes. The high-intensity training program is composed of aerobic exercise sessions (twice per week; Tuesday and Thursday), anaerobic exercise sessions (three times per week; Monday, Wednesday, and Friday), and flexibility exercise sessions (five times per week). During the 6 week high-intensity training program, drug ingestion (L-arginine or placebo) was conducted in the first two weeks, wash out (two weeks) followed it, and drug ingestion (L-arginine or placebo) was carried out again in the last two weeks. The crossover design was used for the experiment so all study subjects were assigned to either the L-arginine intake group (the treatment group) or the placebo group (the control group). Each subject ingested 3g per day. This study confirmed the significant effects of L-arginine supplementation on muscle damage indices, fatigue indices, and antioxidants using blood samples. Additionally, FMD was analyzed to evaluate vascular endothelial cell functions and canoe performance was examined using the canoe ergometer. The results of this study showed that L-arginine intake did not have direct effects on the levels of ammonia, IP, and CK. The level of LDH decreased significantly more in the ARG group than in the PLA group due to L-arginine supplementation. Moreover, L-arginine supplementation did not change total NO, d-ROMs, BAP, and FMD significantly. Lastly, the results of the 500m canoe ergometer, which was conducted to evaluate the canoe performance, revealed that L-arginine did not have direct effects on total time, stroke distance, and mean velocity. However, L-arginine supplementation significantly improved muscle damage indices, fatigue indices, antioxidants, FMD, and canoe performance. Therefore, it is believed that additional studies are needed for examining the potential effects of L-arginine supplementation athletic performance enhancement.